2009
DOI: 10.1007/s11010-009-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-translational strategies for the elevation of Nm23-H1 metastasis suppressor gene expression

Abstract: Interruption of the tumor metastatic process is a new, thought provoking molecular target for the treatment of cancer. The Nm23-H1 metastasis suppressor gene stands as a validated molecular target owing to its reduced expression in many aggressive human tumors, and the reduction in meta-static potential in vivo upon re-expression in multiple cell lines. Several compounds have been identified which elevate Nm23-H1 expression in vitro including indomethacin, γ Linolenic Acid, trichostatin A, 5-aza-deoxycytidine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The presence of high concentrations NM23-H1 has been shown to be an indicator of prognosis in many cancers17, 2027, with its highest concentration in the non-tumorigenic state and a significantly reduced level in the metastatic state17. Over-expression of NM23-H1 can eradicate tumor cell motility and invasion28 while promoting cellular differentiation, and shuts down anchorage-independent growth29.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of high concentrations NM23-H1 has been shown to be an indicator of prognosis in many cancers17, 2027, with its highest concentration in the non-tumorigenic state and a significantly reduced level in the metastatic state17. Over-expression of NM23-H1 can eradicate tumor cell motility and invasion28 while promoting cellular differentiation, and shuts down anchorage-independent growth29.…”
Section: Resultsmentioning
confidence: 99%
“…While this compound appears to impact invasiveness for some cancer cells by altering the DNA methylation status of a CpG island in the Nm23-H1 promoter, this is not the case in other cancer cells (23), suggesting that the effect of the compound may be cell type specific. Several other compounds in clinical use also upregulate Nm23-H1 expression in vitro and in vivo (23).…”
Section: Discussionmentioning
confidence: 97%
“…While this compound appears to impact invasiveness for some cancer cells by altering the DNA methylation status of a CpG island in the Nm23-H1 promoter, this is not the case in other cancer cells (23), suggesting that the effect of the compound may be cell type specific. Several other compounds in clinical use also upregulate Nm23-H1 expression in vitro and in vivo (23). Therefore, our data provide a rationale for pursuing additional studies to determine whether pharmacologic interventions resulting in cytoplasmic overexpression of Nm23-H1, or which target Nm23-H1-associated signal transduction, interfere with KSHV-associated invasiveness.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, histidine kinases are well known in bacteria and lower eukaryotes, in which they form a major signal transduction pathway to extracellular events (two-component-signaltransduction systems) [82,83]. In model studies with human breast carcinoma cells, it could be shown that the metastasis potential was decreased upon treatment with compounds that were capable to increase NDKA expression [84]. Recently, pharmaceutical companies have identified histidine kinase inhibitors as a next generation approach to antibioticresistant bacterial infection [85], and these technologies and agents may be readily transferable to the cancer field, once anti-metastatic activity is proven.…”
Section: Discussionmentioning
confidence: 99%